The influence of green marketing and environmental concerns on purchase intention in thrift shops - M Abiyyu Alwansyah Hsb; Laylan Syafina; Murdifin Azhar (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of green marketing and environmental concerns on the purchase intention of thrift products among Generation Z in Medan City. This research is motivated by the high interest in thrifting amidst the controversy surrounding the regulation banning the import of used clothing. The research method used is quantitative associative. The sample consisted of 99 Generation Z respondents in Medan City selected using accidental sampling technique. Data analysis used multiple linear regression with the help of SPSS. The results showed that partially, green marketing did not have a significant effect on purchase intention, indicating the ineffectiveness of green promotion due to product legality issues. Conversely, environmental concerns had a positive and significant effect, proving that purchasing decisions were driven more by consumers' internal environmental awareness. Simultaneously, both variables had a significant effect on purchase intention with a contribution of 28.9%. The study concluded that personal moral motives were more dominant than marketing strategies in encouraging thrift purchasing behavior.